Analisis Faktor Yang Mempengaruhi Tingkat Kemandirian Lansia Dalam Melakukan Activity Daily Living - Anis Sulalah; Dodik hartono; Achmad Kusyairi (Pusat riset dan Inovasi Nasional, 2023)
The elderly is a vulnerable group that has a very high dependency rate. The elderly has various health problems such as degenerative diseases and decreased productivity so that it can cause a decrease in independence in carrying out daily activities (Activities Daily Living).This research strategy combines a cross-sectional approach with correlational analysis. Simple random sampling is the method used for sampling. employing the logistic regression test. examined respondents' perceptions of senior citizens' independence, using a sample size of 45 respondents.The results of this study found that there was a relationship between all factors that could be done both from family support, cognitive function, and anxiety with a p value of 0.05 while the dominant factor related to the independence of the elderly was the anxiety factor with a p value of 0.005 a 0.05 and OR value =248792879.8 Can guarantee that family support, cognitive function, and can increase the independence of the elderly, but the most dominant factor for independence is the anxiety factor.To ensure that body parts can move and there is no immobility disorder, it is expected of the aged to continue with everyday activities. They are also expected to maintain their health by visiting an integrated health center, a public health center, or other healthcare facilities.